2014
DOI: 10.1002/ptr.5237
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Combinatory Antimicrobial Effect of Plumbagin with Oxacillin and Tetracycline against Staphylococcus aureus

Abstract: Plumbagin (5-hydroxy-2-methyl-1,4-naphthoquinone), a bicyclic naphthoquinone naturally distributed among Plumbago species, has been reported to have antimicrobial activity against a wide range of microorganisms. In this study, plumbagin was examined for its combinatory antimicrobial effect with tetracycline or oxacillin against nine strains of Staphylococcus aureus, including its methicillin- and multidrug-resistant strains. Minimum inhibitory concentrations were determined through the broth microdilution meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 12 publications
(15 reference statements)
0
13
0
Order By: Relevance
“…) and plumbagin (5‐hydroxy‐2‐methyl‐1,4‐naphthoquinone), a bicyclic naphthoquinone from Plumbago species, which are active in combination with oxacillin and tetracycline against MRSA (Rondevaldova et al . ). Currently, antibiotic resistance and biofilm formation are two virulence factors that hugely contribute to high levels of mortality caused by MRSA infections (Archer et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…) and plumbagin (5‐hydroxy‐2‐methyl‐1,4‐naphthoquinone), a bicyclic naphthoquinone from Plumbago species, which are active in combination with oxacillin and tetracycline against MRSA (Rondevaldova et al . ). Currently, antibiotic resistance and biofilm formation are two virulence factors that hugely contribute to high levels of mortality caused by MRSA infections (Archer et al .…”
Section: Discussionmentioning
confidence: 97%
“…The naphthoquinones are a promising group of molecules that have been explored because of their wide biological active profile as anticancer (Khaw et al 2015), antiparasitic Jorqueira et al 2006;Silva-Jr et al 2008), antifungal (Campos et al 2015) and antibacterial (Tabata et al 1982;Gafner et al 1996;Oliveira et al 2001) compounds. The literature contains several reports concerning synthetic derivatives that are (Rondevaldova et al 2015). Currently, antibiotic resistance and biofilm formation are two virulence factors that hugely contribute to high levels of mortality caused by MRSA infections (Archer et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The combination effect of antibiotics and AEHS was determined by checkerboard assay and evaluated algebraically based on the sum of the fractional inhibitory concentration ( P FIC) indices as previously described (Vuuren & Viljoen 2011;Rondevaldova et al 2015). In brief, twofold serial dilutions of each CLA, AMX and MTZ prepared in horizontal rows of micro-titer plate were subsequently cross-diluted vertically by twofold serial dilutions of AEHS.…”
Section: Combination Effect Of Aehs With Standard Antibioticsmentioning
confidence: 99%
“…Previously, Rondevaldova et al . () reported its additive or synergistic anti‐staphylococcal activity in combination with tetracycline or oxacillin. Though anti‐staphylococcal activity of plumbagin is already known (Lajubutu et al .…”
Section: Introductionmentioning
confidence: 99%
“…The phytochemical is reported to show various pharmacological properties such as anti-inflammatory, anti-cancer and anti-microbial activities (Tilak et al 2004;Padhye et al 2012;Sunil et al 2012;Hafeez et al 2013). Previously, Rondevaldova et al (2015) reported its additive or synergistic anti-staphylococcal activity in combination with tetracycline or oxacillin. Though anti-staphylococcal activity of plumbagin is already known (Lajubutu et al 1995;Jeyachandran et al 2009), no study reported its activity against clinically problematic MDR MRSA isolates.…”
Section: Introductionmentioning
confidence: 99%